Amyloid (AL) in an octogenarian diagnosed by abdominal wall fat biopsy. Issue 736 (February 1987) - Mallinson, W. J.; Corrado, O. J.; Milkins, S. R.
Abstract : Systemic amyloid (AL) was diagnosed by abdominal wall fat biopsy in an 81 year old woman presenting with severe postural hypotension. The advantages of this little-used diagnostic method are discussed.